Formation of TiO2 nanotubes and deposition of silver nanoparticle and reduced graphene oxide: Antibacterial and biocompatibility behavior - Turu, Irem Cemre; Bayraktar, Semih; Akgul, Busra; Ilhan-Sungur, Esra; Abamor, Emrah Sefik; Cansever, Nurhan (ELSEVIER SCIENCE SA, 2023)
The biocompatibility of titanium alloys used as implant material is enhanced by TiO2 nanotubes. Particles deposited on TiO2 nanotubes for antibacterial purposes may affect bacterial attachment and biofilm formation differently, thus being effective in preventing formation or development of implant-related infections. To investigate this aspect, TiO2 nanotubes were produced on Ti6Al4V-ELI by anodic oxidation (30 V-1 h, ethylene glycol, 0.5 % NH4F, 5 % H2O). Silver nanoparticles (AgNP) and reduced graphene oxide (rGO) were electrophoretically deposited on nanotube surfaces. The antibacterial activity and biocompatibility of the samples were investigated. 96-h tests with S. aureus revealed that TiO2 NT-AgNP and TiO2 NT-rGO improved antibacterial activity and TiO2 NT-rGO did not cause any morphological damage on bacteria. As a result of biocompatibility tests on L929 fibroblast cells for 72 h with MTT method, none of the samples showed cytotoxicity, instead, AgNP and rGO had a positive effect on cell adhesion and proliferation without giving any adverse effects on cell morphology. This study provides new insights into the effect of nanotube formation and nanoparticle decoration on the Ti6Al4V-ELI surface on interaction of bacterial biofilm and cell. These encouraging findings will contribute to development of AgNP- and rGO-deposited TiO2 NTs to prevent various implant-related health problems. In further studies, TiO2 NT-AgNP can be suggested to reduce bacterial attachment, and TiO2 NT-rGO can be recommended to delay maturation of bacterial biofilm.
Keywords: TiO 2 nanotube; AgNP; rGO; Antibacterial; Biofilm; MTT assay; STAPHYLOCOCCUS-AUREUS; ENHANCED ANTIBACTERIAL; IN-VITRO; TITANIUM; BACTERIA; IMPLANT; EPIDERMIDIS; TOXICITY; FILMS; Materials Science; Physics